1996
DOI: 10.1111/j.1471-0528.1996.tb09736.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection in pregnancy

Abstract: Objective To evaluate the clinical aspects of hepatitis C virus (HCV) liver disease in anti‐HCV + ve mothers, both during pregnancy and six months after delivery, and to assess the outcome of pregnancy. Setting Obstetric department for high risk pregnancies of the University of Padova, Italy. Participants Seventeen hundred consecutive pregnant women were studied. Methods Each woman underwent the following: 1. serological screening for hepatitis surface antigen (HBsAg), antibodies to HCV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(30 citation statements)
references
References 28 publications
4
25
0
Order By: Relevance
“…[15][16][17] The rate of spontaneous abortion was approximately the same as in the normal population. There was no increase in typical obstetric complications such as gestational diabetes and hypertension.…”
Section: Issues Relating To Pregnancy and Chronic Hepatitis Cmentioning
confidence: 67%
“…[15][16][17] The rate of spontaneous abortion was approximately the same as in the normal population. There was no increase in typical obstetric complications such as gestational diabetes and hypertension.…”
Section: Issues Relating To Pregnancy and Chronic Hepatitis Cmentioning
confidence: 67%
“…33 This observation is in agreement with reports that the maternal/placental unit manufactures interferon, possibly decreasing hepatic inflammation during pregnancy. 34 The risk for vertical transmission and maternal or fetal outcome in patients who previously underwent OLT has not been systematically reported.…”
Section: Discussionmentioning
confidence: 99%
“…The limited data that are available come to varying conclusions. While maternal HCV was not associated with obstetric complications in a number of studies [23,38,39], one reported that women with HCV viremia had an increased risk of premature rupture of membranes [40]. Two studies demonstrated an increased risk of gestational diabetes in pregnant women with HCV [41,42].…”
Section: For Reprint Orders Please Contact: Reprints@futuremedicinecommentioning
confidence: 99%
“…A study in HIV-positive women demonstrated higher rates of low birth weight children (<2500 g) born to those coinfected with HCV [42], and another demonstrated higher rates of neonatal intensive care unit admission and need for assisted ventilation [41]. Apgar scores on the other hand, appear to be similar regardless of maternal HCV status [20,23,38,41]. Owing to their narrow scope and retrospective nature, conclusions that can be drawn from these studies are limited.…”
Section: For Reprint Orders Please Contact: Reprints@futuremedicinecommentioning
confidence: 99%
See 1 more Smart Citation